2010
DOI: 10.1093/pasj/62.5.1177
|View full text |Cite
|
Sign up to set email alerts
|

What Kinds of Accretion Disks Are There in the Nuclei of Radio Galaxies?

Abstract: It seems to be a widely accepted opinion that the types of accretion disks (or flows) generally realized in the nuclei of radio galaxies and in further lower mass-accretion rate nuclei are inner, hot, optically thin, radiatively inefficient accretion flows (RIAFs) surrounded by outer, cool, optically thick, standard-type accretion disks. However, observational evidence for the existence of such outer cool disks in these nuclei is rather poor. Instead, recent observations sometime suggest the existence of inner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…When considering the low-excitation sources, it is evident that NGC 315 is not the only object showing a subparsec scale transition, which is observed also in other two lowluminosity jets, NGC 1052 and NGC 4261. At least in the case of NGC 4261, this distance is also much smaller than the Bondi radius, estimated by Balmaverde et al (2008) to be ∼32 pc, but it may match the actual extent of the hot gas phase as inferred from a spectral fitting performed by Kaburaki et al (2010). None of the jets in HEG presents a sub-parsec scale transition, and the transition distances seem to be shifted to larger radii than in LEG.…”
Section: Transition Distancementioning
confidence: 63%
“…When considering the low-excitation sources, it is evident that NGC 315 is not the only object showing a subparsec scale transition, which is observed also in other two lowluminosity jets, NGC 1052 and NGC 4261. At least in the case of NGC 4261, this distance is also much smaller than the Bondi radius, estimated by Balmaverde et al (2008) to be ∼32 pc, but it may match the actual extent of the hot gas phase as inferred from a spectral fitting performed by Kaburaki et al (2010). None of the jets in HEG presents a sub-parsec scale transition, and the transition distances seem to be shifted to larger radii than in LEG.…”
Section: Transition Distancementioning
confidence: 63%
“…The importance of magnetic diffusivity has been studied in several accreting systems, such as protostellar discs (Stone et al 2000; Fleming & Stone 2003), discs in dwarf nova systems (Gammie & Menou 1998), the discs around black holes (Kudoh & Kaburaki 1996) and the Galactic Centre (Melia & Kowalenkov 2001; Kaburaki et al 2010). Moreover, two‐ and three‐dimensional magnetohydrodynamics (MHD) simulations have shown that resistive dissipation is one of the crucial processes that determine the saturation amplitude of the magnetorotational instability (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…The resistive diffusion of magnetic field is important in some systems, such as the protostellar discs Fleming & Stone 2003), discs in dwarf nova systems (Gammie & Menou 1998), the discs around black holes (Kudoh & Kaburaki 1996), and Galactic center (Melia & Kowalenkov 2001;Kaburaki et al 2010). Also, two and three dimensional simulations of local shearing box have shown that resistive dissipation is one of the crucial processes that determines the saturation amplitude of the magnetorotational instability (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent works represent importance of magnetic diffusivity in accretion discs (e.g. Kuwabara et al 2000;Kaburaki 2000 ;Kaburaki et al 2002;Sh04;Ghanbari et al 2007;Krasnopolsky et al 2010;Kaburaki et al 2010). Sh04 studied a quasi-spherical accretion flow that dominant mechanism of energy dissipation was assumed to be the magnetic diffusivity due to turbulence in the accretion flow and the viscosity of the fluid was completely neglected.…”
Section: Introductionmentioning
confidence: 99%